Quand l’exil à l’intérieur du pays engendre la Peur - Maftei, Mara Magda (Romanica Silesiana)
In this short paper, we propose to analyze the Fear experienced by the Romanian intellectual when Secret Police could knock at his door at any time of night or day to imprison and torture him. Inoculate Fear represented the main instrument of torture practiced by the communist Secret Police. Examples extracted from writings of two intellectuals subjected to communist terror (N. Steinhardt and C. Noica) will show us the states of mind man experiences from the moment the idea of Fear seeps into his head to different “strategies” imagined in order to live with it. Keywords : exile, communism, prison, Fear, Nicolae Steinhardt, Constantin Noica